A scheme for anaerobic digestion modelling and ADM1 model calibration - Liu, Yanxin; Jiang, Ying; Bortone, Immacolata (Associazione Italiana Di Ingegneria Chimica (AIDIC), 2022)
Anaerobic digestion (AD) is a technology that produces biogas, also known as renewable natural gas, from organic waste materials under the activity of anaerobic microorganisms. In recent years, an increasing attention on energy produced from renewable resources has led to the need and development of tools helping with improving the process performance and design of AD, such as the Anaerobic Digestion Model No.1 (ADM1). ADM1 is a process-based model that can predict the biogas yield and identify potential prohibitions in the AD process from the properties of the feedstock and inoculum. Initial values of state variables and model parameters need to be calibrated when applying ADM1 to a particular feedstock. In this study, an ADM1 model using differential algebraic equations (DAE) system, called DAE ADM1, was developed. Specifically, the influence of the initial values of AD process state variables on the calibration of model stoichiometric and kinetic parameters were investigated, by comparing them with literature data, by highlighting their high impact on the model setup.